2013
DOI: 10.1016/j.drugalcdep.2012.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive deficits in long-term anabolic-androgenic steroid users

Abstract: Background Millions of individuals worldwide have used anabolic-androgenic steroids (AAS) to gain muscle or improve athletic performance. Recently, in vitro investigations have suggested that supraphysiologic AAS doses cause apoptosis of neuronal cells. These findings raise the possibility, apparently still untested, that humans using high-dose AAS might eventually develop cognitive deficits. Methods We administered five cognitive tests from the computerized CANTAB battery (Pattern Recognition Memory, Verbal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
1
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(110 citation statements)
references
References 38 publications
4
92
1
13
Order By: Relevance
“…Evidence suggests that an increasing number of deaths of athletes in the age group of 20 -30 years is due to heart diseases resulting from AAS use [13]. AAS are toxic to the cardiac tissue and leads to cardiomyopathy with impaired systolic and diastolic functions [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that an increasing number of deaths of athletes in the age group of 20 -30 years is due to heart diseases resulting from AAS use [13]. AAS are toxic to the cardiac tissue and leads to cardiomyopathy with impaired systolic and diastolic functions [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that addiction to drugs or behaviours such as gambling can lead to impaired cognitive skills [25][26][27][28]. Such findings provide a good rationale for why this might also be the case among those addicted to videogames.…”
Section: Introductionmentioning
confidence: 86%
“…These were large effects on pattern recognition and Memory. Long-term AAS users underperformed nonusers by almost one standard deviation and performance on this test declined markedly with increasing lifetime AAS dose [35].…”
Section: The Downside Of Aasmentioning
confidence: 92%